FAKTOR - FAKTOR YANG MEMPENGARUHI TERHADAP JUMLAH KREDIT YANG DISALURKAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013) - Muhamad Rizal Firmansah, 11.05.52.0023; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2016)
The Bank is a financial institution which functions as a financial intermediary between parties that surplus funds (surplus units) and those who lack funds (deficit units). Through banks with excess funds, then the funds can be distributed to the parties that need and will provide benefits for both sides. As has been stated also in the Law No.10 of 1998 on banking, it can be concluded that the bank can act as financial intermediaries by raising funds from the public that surplus funds in various forms of deposits. For that to know the internal factors of the banking side that is estimated to affect banks in channeling capital credit works, namely third-party funds, CAR, ROA, and LDR NPL. The population used in this study are all the banks that listing on the Indonesia Stock Exchange during 2011-2013. And for research purposes, the use of samples by purposive sampling method in order to get 75 companies that meet the criteria. Data used is secondary data derived from financial statements published and downloaded via the official website of the Indonesian Stock Exchange. Years of observation in this study is from 2011 to 2013. The results showed that the DPK, CAR, LDR, significant positive effect on total outstanding loans. While ROA significant negative effect, and NPL significant negative effect on the number of outstanding loans.Keywords: DPK, CAR, ROA, NPL, LDR, Credit